Moderating Environmental, Social, and Governance (ESG) Performance in The Relationship between Profitability and Firm Value of Listed Companies on The Stock Exchange of Thailand - Thananchai, Aranphong; Somsoda, Jintana (Executive Journal, 2025)
This study aims to examine the impact of Environmental, Social, and Governance (ESG) practices on the relationship between profitability and firm value of companies listed on the Stock Exchange of Thailand. The study utilizes secondary data from 2021-2023, with a sample of 331 firm-year observations selected for analysis based on the availability of relevant variables disclosed in the Bloomberg database. Multiple regression analysis was employed to test the hypotheses. The findings reveal that profitability has a positive and statistically significant relationship with firm value. Furthermore, ESG practices significantly influence the relationship between profitability and firm value. Specifically, the interaction between profitability and environmental performance has a significantly positive effect on firm value. In contrast, the interactions between profitability and both social and governance performance show significantly negative effects on firm value.